Application of the Simple Multi-Attribute Rating Technique (SMART) for Selecting Compatible Earthquake Time Series in Liquefaction Analysis Support: Case Study in Serpong, Tangerang, Indonesia - Haifani, Akhmad Muktaf; Setiadipura, Topan; Prakoso, Widjojo A. (Geological Agency, 2026)
The earthquake hazard must be mitigated at the prospective nuclear power plant site in Serpong, Tangerang, to avoid damage to the nuclear installation infrastructure, especially the possibility of liquefaction. This study combines Probabilistic Seismic Hazard Analysis (PSHA) with Ground Motion Prediction Equation (GMPE) (Abrahamson, 2014), which is used as a probabilistic prediction model. This is to estimate spectral accelerations and Peak Ground Acceleration (PGA) based on earthquake magnitude, distance, and site characteristics. Calculations were carried out using OpenQuake for PHA calculation and Seismomatch for spectra matching analysis, which produced the deaggregation results used to define the target spectrum. Representative time histories were chosen using the SMART technique, which uses ranking and weighting to assure compliance with deaggregated magnitude-distance situations, then refined using spectral matching of 90 records while keeping nonstationary properties. Both shallow crustal and subduction events have a substantial impact on seismic demand, with the 2011 Tohoku earthquake (Mw 9.0, depth 29 km, distance 245.9 km, PGA 0.26 g) appearing as the most compatible scenario and primary contributor to possible site risks. The suggested paradigm provides a realistic solution to site-specific ground motion selection and liquefaction risk assessment, hence promoting nuclear safety and seismic resilience in tectonically active regions.